Sequential treatment of paper and pulp industrial wastewater: Prediction of water quality parameters by Mamdani Fuzzy Logic model and phytotoxicity assessment. (July 2019) - Mazhar, Sadat; Ditta, Allah; Bulgariu, Laura; Ahmad, Iftikhar; Ahmed, Munir; Nadiri, Ata Allah
Abstract: Recycling of industrial wastewater meeting quality standards for agricultural and industrial demands is a viable option. In this study, paper and pulp industrial wastewater were treated with three biological treatments viz. aerobic, anaerobic and sequential (i.e. 20 days of anaerobic followed by 20 days of aerobic cycle), associated with simulation modeling by Mamdani Fuzzy Logic (MFL) model of some selected parameters. Electric air diffuser and minimal salt medium in sealed plastic bottles at control temperature were used for aerobic and anaerobic treatments, respectively. The significant reduction in chemical (COD: 81%) and biological oxygen demand (BOD: 71%), total suspended (TSS: 65%), dissolved solids (TDS: 60%) and turbidity (68%) was recorded during sequential treatment. The treated water was irrigated to determine its phytotoxic effects on seed germination, vigor and seedling growth of mustard ( Brassica campestris ). Sequential treatment greatly reduced phytotoxicity of wastewater and showed the highest germination percentage (90%) compared to aerobic (60%), anaerobic (70%) treatments and untreated wastewater (30%). Regression analysis also endorsed these findings (R 2  = 0.76–0.95 between seed germination, seedling growth and vigor). MFL technique was adopted to simulate sequential treatment process. The results support higher performance of MFL model to predict TDS, TSS, COD, and BOD based on the physico-chemical water quality parameters of raw wastewater, time of treatment and treatment type variation. Based on these findings, we conclude that the sequential treatment could be a more effective strategy for treatment of pulp and paper industrial wastewater with efficiency to be used for agricultural industry without toxic effects. Graphical abstract: Image 10 Highlights: Pulp and paper wastewater was subjected to aerobic, anaerobic and sequential treatment. Sequential treatment significantly reduced COD, BOD, TSS, TDS and turbidity. Mamdani Fuzzy Logic technique was adopted to simulate sequential treatment process. Sequentially treated wastewater improved seed germination, seedling growth and vigor index. Sequential treatment is more efficient as compared to sole aerobic and anaerobic treatment.